Iodosulfonylation of Alkynes under Ultrasound Irradiation - Zhou, Chuanjiang; Zeng, Xianghua (Synthesis, 2021)
(E)-β-Iodo vinylsulfones are synthesized under ultrasound irradiation using alkynes, sulfonyl hydrazides, potassium iodide and hydrogen peroxide. The key features of this protocol are the speed and efficiency of the reactions, which afford good to excellent yields of the desired products by employing ultrasound as the driving force. Mechanistic studies reveal that a sulfonyl radical intermediate is generated via sulfonyl iodide homolysis.
Keywords: ultrasound; iodosulfonylation; alkynes; one-pot; green chemistry